ATC Mw7.1 Puebla–Morelos earthquake reconnaissance observations: Seismological, geotechnical, ground motions, site effects, and GIS mapping. Issue 2 (December 2020) - Diaz-Fanas, Guillermo; Garini, Evangelia; Ktenidou, Olga-Joan; Gazetas, George; Vaxevanis, Themis; Lan, Yun Jennifer; Heintz, Jon; Ma, Xin; Korre, Evangelia; Valles-Mattox, Rodolfo; Stavridis, Andreas; Kim, Insung; et al.
This article presents the Applied Technology Council (ATC) team's observations following the 2017 Mw 7.1 Puebla–Morelos, Mexico earthquake. The team was deployed in Mexico City to collect seismological, geotechnical, structural, and overall performance information. The focus was on non-ductile concrete structures, to support implementation of recently published FEMA P-2018 procedures and to identify study buildings for incorporation into NIST-funded ATC-134 ongoing project. This article presents seismological data with 71 strong-motion records processed and ready for use in engineering analysis, geotechnical observations, and characterization of sites visited. Analyses of the response of representative soil profiles are presented in the form of acceleration response spectra and seismic amplification at the ground surface. A comparison of the same analysis using records from the 1985 Michoacán Ms 8.1 (approximately Mw 8.0) earthquake is also discussed. The ATC team composed GIS maps with structural and geotechnical characteristics of the inspected sites, including color-coded damage of inspected buildings and estimated soil fundamental period to correlate observed behavior with potential soil–structure interaction resonance effects. Recommendations on further detailed studies based on this comprehensive set of case histories are proposed.